2021
DOI: 10.2196/29120
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Outcome Measurements From Electronic Medical Records: Cross-sectional Study on the Effectiveness of Neural and Nonneural Classifiers

Abstract: Background With the rapid adoption of electronic medical records (EMRs), there is an ever-increasing opportunity to collect data and extract knowledge from EMRs to support patient-centered stroke management. Objective This study aims to compare the effectiveness of state-of-the-art automatic text classification methods in classifying data to support the prediction of clinical patient outcomes and the extraction of patient characteristics from EMRs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Among these, BERT has been found to be particularly widely used in the medical field in general, and for stroke in particular, along with specialized versions fitted to these applications that improve their performance [ 22 , 41 ]. More basic ML algorithms and hybrid approaches with rule-based techniques are still more present than advanced DL networks in the recent research on NLP for stroke, and in some cases, tailored rule-based systems outperformed BERT and its derivatives [ 19 , 22 ]. Support vector machine methods were also found to perform better than BERT in one study [ 19 ], although random forest was reported to have the best performance more frequently than any other ML method in the set of reviewed studies [ 18 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, BERT has been found to be particularly widely used in the medical field in general, and for stroke in particular, along with specialized versions fitted to these applications that improve their performance [ 22 , 41 ]. More basic ML algorithms and hybrid approaches with rule-based techniques are still more present than advanced DL networks in the recent research on NLP for stroke, and in some cases, tailored rule-based systems outperformed BERT and its derivatives [ 19 , 22 ]. Support vector machine methods were also found to perform better than BERT in one study [ 19 ], although random forest was reported to have the best performance more frequently than any other ML method in the set of reviewed studies [ 18 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…More basic ML algorithms and hybrid approaches with rule-based techniques are still more present than advanced DL networks in the recent research on NLP for stroke, and in some cases, tailored rule-based systems outperformed BERT and its derivatives [ 19 , 22 ]. Support vector machine methods were also found to perform better than BERT in one study [ 19 ], although random forest was reported to have the best performance more frequently than any other ML method in the set of reviewed studies [ 18 , 42 , 46 ]. Some of these results may seem unexpected, given the remarkable performance of DL in general, and particularly large language models (LLMs), in other areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, various obstacles such as the lack of interoperability have limited the full use of EHR data to improve the delivery of care. Consequently, existing studies are mostly based on patient data confined to a single EHR system within a single geographic area [ 83 ]. By contrast, administrative data, such as claims data, follow specific standards for both the structure and meaning of the variables contained within a claim, and nearly every health care provider must submit electronic claims in the same format to their payers or clearinghouses.…”
Section: Discussionmentioning
confidence: 99%